PEMBERIAN BERBAGAI PUPUK ORGANIK TERHADAP PERTUMBUHAN DAN PRODUKSI BEBERAPA VARIETAS PADI GOGO (Oryza sativa L.) YANG DITANAM DIANTARA TANAMAN KELAPA SAWIT BELUM MENGHASILKAN - Fetmi Silvina; Arnis en Yulia; Noreza Masri (UIR Press, 2017)
The study aimed to determine the effect of various organic fertilizers on growth and yield of several varieties of upland rice, and the response of upland rice varieties to organic fertilizers under the stands of oil palm trees have not produced (TBM). The researches conducted in March until July 2016. This study was a randomized block design factorial trial with two factors and three replications, the first factor was some upland rice variety consist of ; Inpago 8 (V1), Situ Bagendit (V2), and Inpago 9 (V3) and the second factor was the variety of organic fertilizers such as; without organic fertilizer (BO0), compost of oil palm empty fruit bunches (BO1), chicken manure (BO2), Kirinyuh or green manure (BO3). Data were analyzed by ANOVA and a further test of Duncan’s multiple range test (DNMRT) level of 5%. The results showed that the varieties Situ Bagendit gave the best response to organic fertilizer by weight of dry milled grain at 4.6 tonnes/ha in the giving of chicken manure.